Autonomous weapons systems and the protection of the human person an international law analysis - Mauri, Diego (Cheltenham, UK Northampton, MA, USA Edward Elgar Publishing, 2022)
roviding a much-needed study of the weapons paradox in the case of autonomous weapons, this book is a detailed and comprehensive account of the current debate over the use of autonomous weapons {u2013} should some form of regulation be applied or a total ban be enforced? How can compliance with existing rules be ensured? Can responsibility be properly allocated? To what extent do concepts such as {u2018}human dignity{u2019} and {u2018}humanity{u2019} provide legal guidance in coping with technology? This book tackles these momentous challenges and strives to provide sound answers by elaborating on international law and proposing normative solutions for current and future human{u2013}machine interactions in this critical field. Diego Mauri expertly explains the complex new technological research involved in autonomous weaponry, with particular focus on technological developments that have elicited intense debates among diplomats, military experts, scientists, philosophers, and international lawyers.
Foreword -- 1. Introduction: Autonomous Weapons Systems and the Protection of the Human Person -- 2. Sketching the debate -- 3. Autonomous weapons systems under international human rights law -- 4. Autonomous weapons systems under international humanitarian law -- 5. Autonomous weapons systems and the {u2018}accountability gap{u2019} conundrum -- 6. Building the bridge to the future -- Bibliography -- Index
Includes bibliographical references and index.
Keywords: Autonomous weapons systems (International law) -- Electronic book; Humanitarian law; Personnes (Droit international); Persons (International law); Autonomous weapons systems (International law); Humanitarian law; Persons (International law)